The Impact of Perceived Social Media Interactivity on Brand Trust. The Mediating Role of Perceived Social Media Agility and the Moderating Role of Brand Value - Bozkurt, Siddik; Gligor, David; Ozer, Serhat; Sarp, Serap; Srivastava, Rajesh (Palgrave Macmillan Ltd, 2023)
Although earlier studies shed light on the significance of perceived social media interactivity, its impact on perceived social media agility and brand trust has yet to be thoroughly investigated. The current study addresses this gap by examining the complex relationship between perceived social media interactivity, brand trust, perceived social media agility, and brand value. To further unpack these complex relationships, the current study investigates the role of gender as a moderating variable on the moderation effect of brand value between perceived social media interactivity and perceived social media agility. In this regard, an online survey (N = 275) was conducted to measure the constructs of interest. PROCESS Models 1, 3, and 4 were used to test the research hypotheses. The results show that individuals perceive highly interactive brands as more agile on social media, leading to high brand trust levels. The results also indicate that the positive link between perceived social media interactivity and perceived social media agility is contingent on consumers' perceived brand value. The results further display that the conditional effect of perceived social media interactivity on perceived social media agility as a function of brand value is moderated by consumers' gender. Most interestingly, the conditional effect of perceived social media interactivity on perceived social media agility as a function of brand value is only significant for men.
Sarp, Serap/0000-0002-2560-4105; Ozer, Serhat/0000-0001-7626-6487
Keywords: Perceived Brand Interactivity; Perceived Social Media Agility; Brand Trust; Brand Value; Gender; Process Models